Transmitted drug resistance and antiretroviral treatment outcomes in non-subtype B HIV-1-infected patients in south east asia - Praphan Phanuphak (2018)
BACKGROUND: We compared treatment outcomes of transmitted drug resistance (TDR) in patients on fully or partially sensitive drug regimens. METHODS: Factors associated with survival and failure were analyzed using Cox proportional hazards and discrete time conditional logistic models. RESULTS: TDR, found in 60 (4.1%) of 1471 Asian treatment-naive patients, was one of the significant predictors of failure. Patients with TDR to > 1 drug in their regimen were > 3 times as likely to fail compared to no TDR. CONCLUSIONS: TDR was associated with failure in the context of non-fully sensitive regimens. Efforts are needed to incorporate resistance testing into national treatment programs. © 2013 by Lippincott Williams and Wilkins.